The crusader : Ronald Reagan and the fall of communism - Kengor, Paul, 1966- (New York : Regan Books, 2006)
"In this dramatic meditation on the life of Ronald Reagan, historian Paul Kengor presents an account of the fortieth president that has never been written - one that details Reagan's campaign against the Soviet Union, which lasted for more than forty years. Tracing Reagan's anti-Communist sentiment to his days as president of the Screen Actors Guild, Kengor illuminates how this experience first emboldened the actor to speak out against the oppression of the Soviet Union and describes Reagan's multifaceted efforts to prevent Communism from taking hold in Hollywood. Ultimately his SAG tenure paved the way for his burgeoning political career, which, from its inception, had but one purpose: the end of Communism.".
"Utilizing reams of recently declassified documents, Kengor assembles a striking mosaic of Reagan's words and actions that toppled the Soviet Union. From Reagan's covert support of the rebels who defeated the Soviets in Afghanistan to his secret oil collusion with Saudi Arabia that devastated the Soviet economy, Kengor reveals how Reagan's eight years in office did more to bring down the Soviet Union than any single administration in the history of the Cold War. With painstaking detail, he also explains Reagan's crucial move to escalate the arms race with the Kremlin, a decision that, though politically unpopular, proved vital to the Soviets' eventual downfall.".
"Revisiting many of the administration's principal characters, Kengor speaks with the individuals who helped shape foreign policy under Reagan. These testimonies give unfettered access into the hearts and minds of those closest to Reagan, revealing how this group translated Reagan's ideas into a comprehensive strategy to destroy the Soviet Union. In addition, Kengor delves into never-before-studied Soviet documents and propaganda, uncovering how the other side perceived Reagan's advances and attempted to counter his progress with its unique brand of disinformation. Also told here is an incendiary revelation of the liberal American politician who reportedly reached out to the Soviets to derail Reagan's 1984 bid for reelection."--BOOK JACKET.
The Early Years -- Rock River Rescuer -- Reagan's Long March: The 1940s -- The TV Crusade: 1950 to mid-1960s -- Cold War Governor: Late 1960s -- Breaking the Mold: 1970s -- "Let's Make America Great Again": 1980 -- The First Term -- First Priorities: January to November 1981 -- Poland Explodes: December 1981 -- Commencing the Crusade: January to June 1982 -- The Vatican and Westminster: June 7-8, 1982 -- Plans and the Pipeline: Mid-June to December 1982 -- The Hottest Year in a Cold War: 1983 -- Grenada and Winning: October to December 1983 -- Winning the Second Term: 1984 -- The Second Term -- The Emergence of Mikhail Gorbachev: March 1985 -- Afghanistan, the Arms Race, and Gorbachev: April to November 1985 -- Conspiracies and Stingers: Late 1985 to 1986 -- Calling for Liberation: 1987 -- "Our formula for completing our crusade": 1988 -- The Fall of the Soviet Empire -- The March of Freedom: 1989 -- The Coroner Comes to the Kremlin: 1990-1991 -- Drifting Back -- Text of KGB Letter on Senator Ted Kennedy.
Includes bibliographical references (p. [321]-396) and index.
Keywords: Reagan, Ronald -- Political and social views; Reagan, Ronald -- Influence; United States -- Foreign relations -- 1981-1989.; Communism -- History -- 20th century; Communism -- Soviet Union; United States -- Foreign relations -- Soviet Union; Soviet Union -- Foreign relations -- United States; United States -- Foreign relations -- Communist countries; Communist countries -- Foreign relations -- United States; United States -- Politics and government -- 1981-1989.; Reagan, Ronald; Reagan, Ronald -- Influence; Communisme -- Histoire; Communisme -- URSS; x -- 1981-1989.; x -- URSS; URSS -- z; x -- Pays socialistes; Pays socialistes -- z; x